Topoisomerase‐1 and ‐2A gene copy numbers are elevated in mismatch repair‐proficient colorectal cancers - Sønderstrup, Ida Marie Heeholm (Mol Oncol, 2015)
INTRODUCTION: Topoisomerase 1 (TOP1) and 2A (TOP2A) are potential predictive biomarkers for irinotecan and anthracycline treatment, respectively, in colorectal cancer (CRC), and we have recently reported a high frequency of gene gain of the TOP1 and TOP2A genes in CRC. Furthermore, Mismatch Repair (MMR) subtypes of CRC have been associated with benefit from adjuvant chemotherapy of primary CRC. Given the involvement of the topoisomerase enzymes in DNA replication and repair, we raised the hypothesis that an association may exist between TOP gene copy numbers and MMR proficiency/deficiency in CRC. MATERIAL AND METHODS: Test cohort: FISH analysis with an in‐house TOP1/CEN20 probe mix and a commercially available TOP2A/CEN17 (Dako, Glostrup, Denmark) probe mix was performed on archival formalin fixed paraffin embedded (FFPE) tissue samples from 18 patients with proficient MMR (pMMR) CRC and 18 patients with deficient MMR (dMMR) CRC. TOP1 and TOP2A gene copy numbers and their ratios per nucleus were correlated with MMR status using the Mann–Whitney test. Validation cohort: FFPE samples from 154 patients with primary stage III CRC (originally included in the RANX05 study) were classified according to MMR status by immunohistochemical analysis using validated antibodies for MLH1, MLH2, MSH6 and PMS2, and information on TOP1, CEN20, TOP2A and CEN17 status was previously published for this cohort. RESULTS: The observed TOP1 gene copy numbers in the 36 CRC test cohort were significantly greater (p < 0.01) in the pMMR subgroup (mean: 3.84, SD: 2.03) than in the dMMR subgroup (mean: 1.50, SD: 0.12). Similarly, the TOP2A copy numbers were significantly greater (p < 0.01) in the pMMR subgroup (mean: 1.99, SD: 0.52) than in the dMMR subgroup (mean: 1.52, SD: 0.10). These findings were confirmed in the validation cohort, where in the pMMR subgroup 51% had ≥2 extra TOP1 copies per cell, while all tumors classified as dMMR had diploid TOP1 status and mean TOP2A copy numbers were 2.30 (SD: 1.36) and 1.80 (SD: 0.31) (p = 0.01) in the pMMR subgroup vs. dMMR subgroup, respectively. DISCUSSION AND CONCLUSION: Our results show that TOP1 and TOP2A gene copy numbers are increased in the pMMR subgroup. We propose that this preference may reflect a selective pressure to gain and/or maintain the gained extra copies of topoisomerase genes whose products are required to cope with high replication stress present in the pMMR tumors, thereby providing a survival advantage selectively in pMMR tumors. Future studies should test this concept and explore potential differences between pMMR and dMMR tumors in response to Top1 and Top2 inhibitors.